2008
DOI: 10.1007/s00726-008-0094-x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Taurine plays a beneficial role against cadmium-induced oxidative renal dysfunction

Abstract: The present study has been carried out to investigate the role of taurine (2-aminoethanesulfonic acid), a conditionally essential amino acid, in ameliorating cadmium-induced renal dysfunctions in mice. Cadmium chloride (CdCl(2)) has been selected as the source of cadmium. Intraperitoneal administration of CdCl(2 )(at a dose of 4 mg/kg body weight for 3 days) caused significant accumulation of cadmium in renal tissues and lessened kidney weight to body weight ratio. Cadmium administration reduced intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 54 publications
4
46
0
1
Order By: Relevance
“…This has been supported by other studies that associate its protective antioxidant properties with direct scavenging of free radicals and indirect preserving of membrane permeability (22,23). TA has therefore become a promising option to treat chemically induced illnesses (14,(24)(25)(26)(27). Recent investigations have shown that TA protects cells from the toxic effects of cadmium (Cd), paracetamol, and arsenic (As) that are mediated by free-radical attack (28)(29)(30)(31).…”
mentioning
confidence: 75%
“…This has been supported by other studies that associate its protective antioxidant properties with direct scavenging of free radicals and indirect preserving of membrane permeability (22,23). TA has therefore become a promising option to treat chemically induced illnesses (14,(24)(25)(26)(27). Recent investigations have shown that TA protects cells from the toxic effects of cadmium (Cd), paracetamol, and arsenic (As) that are mediated by free-radical attack (28)(29)(30)(31).…”
mentioning
confidence: 75%
“…In several acute and sub-acute treatment studies, TAU acted as a Cd detoxifi er in the blood, liver, and kidney tissues of mice (12,32,33). It possesses one amino (-NH 2 ) and one sulphonate (-SO 3 H) group, which may be responsible for its detoxifying action.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory data were reported for the kidney of a teleost Clarias batrachus and mice treated with TAU. It lowered Cd content in the fi sh and mice, but lipid peroxidation decreased only in mice (12,13).…”
mentioning
confidence: 94%
“…It has been shown that taurine improves endothelial function and inhibits apoptosis of endothelial cell as well as decreases plasma level of LDL, which prevents initiation and progression of atherosclerosis (Fennessy et al, 2003;Murakami et al, 2002). Taurine exhibits antioxidative properties, membrane stabilizing effect, regulates intracellular Ca2+ concentration, inhibits apoptosis, reduces the levels of pro-inflammatory cytokines in various organs and controls blood pressure (Das et al, 2008;Manna et al, 2008;2009). Additionally, the protective effects of taurine against cyclosporine-A-induced oxidative stress and hepatotoxicity have been documented previously (Hagar et al, 2006).…”
Section: Introductionmentioning
confidence: 99%